Polyglandular endocrinopathy type II (Schmidt's syndrome) in a Dobermann pinscher. (3rd August 2016) - Cartwright, J. A.; Stone, J.; Rick, M.; Dunning, M. D.
Abstract : A three‐year‐old, female neutered, Dobermann pinscher was presented for investigation of lethargy, episodic collapse, ataxia and myxoedema. Primary hypothyroidism and primary cortisol‐deficient hypoadrenocorticism were diagnosed based on history, physical examination and compatible hormonal analysis. Increased serum concentrations of thyroglobulin autoantibodies and 21‐hydroxylase autoantibodies indicated an immune‐mediated aetiology. The case was complicated by lymphadenopathy with hand‐mirror lymphocytes, classically identified in lymphoma. A polymerase chain reaction test for antigen receptor rearrangement indicated polyclonality and therefore reactive lymphadenopathy. The dog's clinical signs resolved following introduction of levothyroxine and prednisolone. Prioritising the problem‐based approach in this case facilitated the diagnosis of hypoadrenocorticism in addition to hypothyroidism due to the persistence of clinical signs despite thyroxine replacement. Importantly, atypical adrenal gland dysfunction was not misinterpreted as inadequate therapeutic response to thyroxine supplementation. The observation that polyglandular endocrinopathy type II can occur in dogs suggests that in dogs with a suboptimal response to treatment for hypothyroidism or hypoadrenocorticism comorbid endocrinopathies should be investigated.